رواية المجهول عند المحدثين - داغي, الأستاذ المساعد إبراهيم فتاح قادر القره; الآلاني, الأستاذ المساعد الدكتور عثمان محمود سعيد الله (Sulaimani Journal for Humanities, 2021)
The traditionists have taken great interest in narrating prophetic sayings and the science of narrating them. They have sought to perceive if the traditionist has met the requirements for his narrations to be accepted or he was far from it and thus unworthy of being approved. This cannot not be known unless the traditionist is well-known and familiar to them since this will help them scrutinize his morals, faith, and qualifications. Accordingly, we conducted this study to explore the traditionist's ignorance and its negative impacts on his narration and how this leads to explaining the types of the unknown and judging their narrations and what causes their ignorance of the truth, as well as the differences among the scholars on whatever relates to the unknown traditionist. We hope that what we have achieved makes a contribution, though small, to the great efforts made in the field by our scholars in the service of the prophetic Sunna and its sciences. We pray for Allah's help to count it onto the scale of our virtues and good deeds.